Pelatihan Mindfulness Pada Remaja Karang Taruna Di Rt.08 Rw.19 Sendangmulyo – Semarang - Rusmalia Dewi; Yudi Kurniawan; Gusti Yuli Asih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The aim of this community service is to provide training on Mindfulness to Youth at Karang Taruna RT.08 RW.19 to increase their understanding of themselves regarding their physical and psychological aspects and be able to make conscious decisions and focus on the activities they are carrying out. Mindfulness training is a meditation method used to increase empathy both affectively, cognitively, morally, intrapersonally and interpersonally. The millennial generation (Gen Z) receives a lot of positive and negative information on the internet. Most Gen Z often use the internet and choose not to interact with their friends because they are comfortable with the gadgets they own. Initial interviews obtained from RT.08 mothers and several teenagers showed that the rise in suicide cases on social media reflects the lack of resilience in Gen Z. RT.08 mothers then asked the PkM team of the Psychology faculty to hold training that The aim is to protect Gen Z's mentality from the pressures that arise in today's millennial life journey. The lack of self-understanding and skills possessed by Gen Z makes RT.08 mothers feel worried about the mentality that Gen Z will have in the future. This input made the PkM team want to help find solutions regarding the self-development of youth at the RT.08 Rw.19 Youth Organization through Mindfulness Training. The process was gathered by teenagers at the RT.08 hall and provided material for understanding and practicing Mindfulness in the form of lectures, practices and games and group discussions. The results of the service show that there is an increase in understanding of 51% in youth at Karang Taruna, meaning that increasing understanding of Mindfulness can improve the ability of youth at Karang Taruna to better understand themselves and the surrounding environment so that they can overcome all challenges and obstacles that occur in the process. journey of daily life.